Study of Serum Levels of Leptin, C-Reactive Protein and Nutritional Status in Hemodialysis Patients - Montazerifar, Farzaneh (Iran Red Crescent Med J, 2015)
BACKGROUND: Leptin is secreted by adipose tissue and decreases appetite. However, the role of leptin in the pathogenesis of hemodialysis (HD)-related malnutrition has not been fully evaluated. OBJECTIVES: The aim of study was to investigate the association between the serum leptin levels, serum C-reactive protein (CRP) levels, and nutritional status in hemodialysis patients. PATIENTS AND METHODS: This analytical descriptive study included 45 hemodialysis patients and 40 healthy subjects. Biochemical parameters and serum leptin levels were measured. The nutritional status was evaluated using a food frequency questionnaire (FFQ) and the calculation of the body mass index (BMI). RESULTS: Serum leptin (P < 0.05) and albumin (P < 0.0001) levels and BMI (P < 0.001) of HD patients were significantly lower, while CRP levels were significantly higher than those of controls (P < 0.0001). HD patients consumed the lower daily servings of the food groups compared to the control subjects (P < 0.0001). A significant positive correlation between serum levels of leptin and albumin and BMI was demonstrated. No significant correlations were identified between leptin level, CRP level, and other variables. CONCLUSIONS: The findings suggest that low levels of leptin may be a contributory factor for malnutrition in HD patients. Further studies are required to ascertain the significance of leptin levels in relation to nutritional factors in hemodialysis patients.